Birth controlled : selective reproduction and neoliberal eugenics in South Africa and India - Pande, Amrita (Governing intimacies in the global South., 2022)
This book analyses the world of selective reproduction - interventions that influence reproductive outcomes and allow only some pregnancies to be borne to fruition - by a critical analysis of three modes of controlling birth, namely contraception, reproductive violence, and repro-genetic technologies.